Coping resources and stress due to demands in parents to children with autism spectrum disorder - Sartor, Teresa; Sons, Sarah; Kuhn, Jörg-Tobias; Tröster, Heinrich (Frontiers in Rehabilitation Sciences, 2023)
Parents to children with autism spectrum disorder (ASD) are exposed to numerous demands in their daily lives and exhibit high levels of stress. The present study aims to find out which coping resources are mediators that help parents cope with these demands and which of those coping resources amplify or reduce stress arising from the demands. Studies often only focus on the connection between coping resources and stress without taking the demands into account at the same time. For this reason, a mediation model was set up to answer the research question. Data from a German questionnaire survey with N = 266 parents who have children with ASD (two to 23 years old) were used. Subjectively perceived demands in everyday life (scale "Parental demands in everyday life", Tröster & Lange, 2019), parental stress ("Parental Stress Inventory", Tröster, 2011, based on Abidin's parenting stress model, 1983) and the following coping resources were collected: parental self-efficacy beliefs ("Parents' sense of competence questionnaire", Miller, 2001), available social support of parents (scale "Availability of social support", Tröster, 2011) and parental coping strategies (Brief COPE, Carver, 1997, German translation by Knoll, 2002). An exploratory factor analysis revealed four mediators: dysfunctional coping, functional coping, social support, and selfefficacy. The use of dysfunctional behavior and parental self-efficacy were found to be significant mediators that mediated between daily demands and parental stress. A direct effect of demands on parental stress was also found, implying partial mediation. The two factors of functional coping and support were not found to be significant mediators. Key findings indicate that parental stress resulting from the daily demands of parenting children with ASD can be reduced by high parental self-efficacy and increased by dysfunctional coping. For practice, it can be deduced that dysfunctional coping strategies of parents to children with ASD should be reduced and parental self-2 This is a provisional file, not the final typeset article efficacy should be strengthened in order to reduce stress which arises from the multiple demands in everyday life.